Diagnostic and predictive value of ultrasound and isotope thyroid scanning, alone and in combination, in infants referred with thyroid-stimulating hormone elevation on newborn screening - Lucas-Herald, Angela; Jones, Jeremy; Attaie, Morag; Maroo, Sanjay; Neumann, David; Bradley, Therese; Hermanns, Pia; Pohlenz, Joachim; Donaldson, Malcolm (The Journal of pediatrics, 2014)
OBJECTIVE: To determine the diagnostic and predictive value of ultrasound and radioisotope scans of the thyroid, alone and in combination, during a single visit after initial referral by the screening laboratory with thyroid-stimulating hormone (TSH) elevation. STUDY DESIGN: Retrospective blind review of ultrasound and radioisotope images followed by final diagnosis based on clinical features, biochemistry, imaging, and molecular genetic study. RESULTS: Infants (n = 97; 61 female) with median birthweight 3.38 kg (range 2.04-4.86) and gestation 40 weeks (range 33-42), underwent successful dual thyroid ultrasound and technetium-99m pertechnetate radioisotope scan in a single center. Combined scanning at the initial visit resulted in a correct final diagnosis in 79 of 97 (81%) cases. One patient was misdiagnosed initially as having athyreosis as the result of delayed radioisotope scan and the diagnosis of ectopia made later on diagnostic challenge. The specificity/sensitivity for radioisotope scan and for ultrasound was as follows: 100%/97% and 100%/55% for ectopia (n = 39); 81%/100% and 54%/100% for athyreosis (n = 18); and 89%/90% and 80%/95% for dyshormonogenesis (n = 20). Neither modality, alone or in combination, predicted final diagnosis in eutopic glands due to hypoplasia (n = 4), transient TSH elevation (n = 12), and status still uncertain (n = 4). CONCLUSION: More than 80% of newborn infants with TSH elevation can be diagnosed correctly on initial imaging with combined radioisotope scan and ultrasound. Ultrasound cannot reliably detect thyroid ectopia. Radioisotope scan, especially if performed late, may show no uptake despite the presence of a eutopic gland.
Keywords: retrospektivní studie; Radionuclide Imaging; konziliární vyšetření a konzultace; novorozenec; Humans; ultrasonografie; lidé; prediktivní hodnota testů; Retrospective Studies; hypotyreóza; Hypothyroidism; Radiopharmaceuticals; radioisotopová scintigrafie; multimodální zobrazování; Predictive Value of Tests; Ultrasonography; Female; Male; Multimodal Imaging; Referral and Consultation; Infant, Newborn; Neonatal Screening; mužské pohlaví; Sodium Pertechnetate Tc 99m; ženské pohlaví; 99mTc-technecistan sodný; thyreotropin; Thyrotropin; novorozenecký screening; radiofarmaka